Design, synthesis and evaluation of 3-phenoxypyrazine-2-carboxamide derivatives as potent TGR5 agonists. Issue 6 (27th January 2022) - Zhao, Shizhen; Wang, Le; Wang, Jie; Wang, Chenwei; Zheng, Shaowei; Fu, Yajie; Li, Yunfu; Chen, Wei-Dong; Hou, Ruifang; Yang, Dongbin; Wang, Yan-Dong
Abstract : The most potent compound 18k exhibited excellent hTGR5 agonist activity, which was superior to those of the reference drugs INT-777. In addition, compound 18k could significantly reduce blood glucose levels and stimulate GLP-1 secretion in C57 BL/6 mice. Abstract : TGR5 is emerging as an important and promising target for the treatment of non-alcoholic steatohepatitis, type 2 diabetes mellitus (T2DM), and obesity. A series of novel 3-phenoxypyrazine-2-carboxamide derivatives were designed, synthesized and evaluated in vitro and in vivo . The most potent compounds 18g and 18k exhibited excellent hTGR5 agonist activity, which was superior to those of the reference drug INT-777. In addition, compound 18k could significantly reduce blood glucose levels in C57 BL/6 mice and stimulate GLP-1 secretion in NCI-H716 cells and C57 BL/6 mice.